Hermite-Hadamard type fractional integral inequalities for generalized beta ( r , g )-preinvex functions - Kashuri,Artion (Universidad Católica del Norte, Departamento de Matemáticas, 2017)
Abstract In the present paper, a new class of generalized beta (r, g)-preinvex functions is introduced and some new integral inequalities for the left-hand side of Gauss-Jacobi type quadrature formula involving generalized beta (r, g)-preinvex functions are given. Moreover, some generalizations of Hermite-Hadamard type inequalities for generalized beta (r, g)-preinvex functions via Riemann-Liouville fractional integrals are established. These results not only extend the results appeared in the literature (see (1), (2)), but also provide new estimates on these types.